A PROFISSIONALIZAÇÃO DA FUNÇÃO PÚBLICA SOB A PERSPECTIVA DA NOVA GOVERNANÇA PÚBLICA (ADMPG Journal, 2021)
This research relates the New Public Governance and the Schools of Government, to investigate whether the Schools of Government acting contributes to developing the employee performance in public administration related to the New Public Governance. It was conducted a qualitative research, a case study method was embraced with and a deep interview for data collection, with a state public employee and a federal public employee, who participated in courses at Schools of Government. Comprehending the speech, both were analyzed using the content analysis, in result some themes were identified: i) competencies; ii) development; iii) results; iv) efficiency; v) actualization; vi) training, all related to the interviewee history and associated with the literature review. It was inferred that the Schools of Government contribute to developing the employee performance in public administration because they promote knowledge training on theory, practice, explicit and tacit, the courses show new knowledge related to tasks which are done by the worker and help to develop needed competencies to do public service.